An analysis of finance journal accessibility: Author inclusivity and journal quality - Grossmann, Axel; Lee, Allissa (Journal of Banking & Finance, 2022)
Existing literature suggests that publication space within and across disciplines is unevenly spaced and that “home bias” and “barriers to entry” negatively impact publication potential, possibly limiting journal accessibility and author inclusivity. We investigate these issues within the field of finance, while considering journal quality, adding another dimension to the literature. Among the quality finance journals included in our study, we find little evidence against inclusiveness with respect to the average number of authors per paper or the percentage of unique authors; however, our analysis indicates that geographical diversity differs among the journals. Consistent with the higher proportion of top finance programs in the U.S., Tier 1 journals exhibit a higher authorship concentration in North America, relating journal quality and geographical diversity. Yet, Tier 2 journals demonstrate a broader regional representation than Tier 3 journals, indicating that geographical inclusivity is not driven exclusively by journal quality. Finally, our results consistently suggest that JBF is the most geographically inclusive journal among the 17 quality finance journals in our study.